y = (x+9)^2

y= x^2 + 18x + 81

consider

x^2 + 18x + 81 which is quadratic so then

a = 1 , b = 18 , c = 81

now using the vertex formula for the value of "x", then

x = -b/2a

putting the values we get

x = -18/2

or x = -9

now putting the value of x in original equation , we get

y = (-9)^2 + 18(-9) +81

y = 81 - 162 + 81

y = 162 - 162

y = 0So now

x = -9 y = 0

Hence the vertex is

( -9,0 )

Secure Information

Content will be erased after question is completed.

Enter the email address associated with your account, and we will email you a link to reset your password.

Forgot your password?

Sign Up